Management of land reclamation quality for agricultural use in opencast mining - Terekhov, Yevgen; Litvinov, Yurii; Fenenko, Volodymyr; Drebenstedt, Carsten (Mining of Mineral Deposits, 2021)
Purpose. Theoretical substantiation of principles and development of recommendations for the choice of technological variant to form the quality of lands of technogenic origin, which would ensure rational spending of funds allotted for reclamation and preservation of the reclaimed lands suitability for agricultural use with the highest requirements for agrophysical soil characteristics. Methods. The following methods were used in the process of the research: the method of theoretical generalization and systematization (to determine the characteristics peculiar to the formation of qualitative characteristics of man-made soil using mechanization of reclamation works), analytical (to determine the factors influencing the effectiveness of land reclamation in opencast mining), comparison (to analyze the efficiency of different versions of reclamation works mechanization). Findings. The influence of technical means of reclamation works mechanization on the quality of lands subject to restoration in conditions of opencast mining is analyzed. A methodological approach to the choice of mechanization of land reclamation works in respect to the indicators of the formed quality of technogenic agricultural lands as a factor of their monetary valuation and the level of costs for their reproduction is proposed. Recommendations for quality management of man-made lands by technical support of the process of their consumer properties formation, aimed at achieving a favorable ratio between quality and, accordingly, monetary valuation of man-made lands, on the one hand, and, on the other, – the cost of their reclamation. Originality.A scientific and methodological approach to the choice of technical equipment for reclamation works is proposed, where two factors are considered: reclamation costs and quality of man-made lands, which allows to determine the priority of cost savings or land quality improvement according to the target criterion of reclamation works efficiency. Practical implications. The obtained results are aimed at improving the methodological bases for management of the man-made lands reclamation process based on the choice of its mechanization means. Keywords: land quality, reclamation costs, monetary valuation of lands, reclamation technology, reclamation efficiency